Determinants of Islamic Banking Social Fund Management Efficiency in Indonesia: Two Stages Data Envelopment Window Analysis - Pantas, Pribawa E (Jurnal Ilmiah Ekonomi Islam, 2024)
The presence of Law No. 21 of 2008 concerning Islamic Banking mandates Islamic banking in Indonesia; apart from carrying out fund collection and distribution activities, it also must manage social funds. This is one of the things that differentiates it from practices in conventional banks. This research aims to analyze the level of Efficiency of management of Islamic banking social funds in Indonesia and the factors that influence it using Two-Step Data Envelopment Window Analysis (DEWA) analysis based on the Scale Efficiency assumption in the first stage and the second stage using pooled Tobit regression applied to 9 Islamic banks throughout the 2018 – 2022 period. The result shows that the level of efficiency in managing social funds of Islamic banks in Indonesia shows an improving trend every year. Return on Assets (ROA) has a positive and significant effect on the social efficiency of Islamic banking. Financing to Deposit Ratio (FDR) has no significant effect or does not have a natural effect on the social efficiency of Islamic banking. Capital Adequacy Ratio (CAR) has a negative effect and is significant.